ASSESSMENT OF BIODIVERSITY PATTERNS IN FRESHWATER ECOSYSTEMS: A ZOOLOGICAL PERSPECTIVE - Nilima S. Prabhu; Shailesh Tawade; Madhuri Tayade; Ansariya Rana (The Bioscan, 2026)
India is home to some of the most biodiverse, yet severely threatened, ecological systems on record - freshwater ecosystems such as rivers, lakes, ponds, and wetlands. From a zoological perspective, these systems support a range of faunal groups (fishes, macroinvertebrates, amphibians, and reptiles) that typically demonstrate highly specialized ecological adaptations and levels of endemism. This research study investigated patterns in biodiversity within India's selected freshwater ecosystems. Specifically, the study examined species richness, species diversity, community composition, as well as relationships between key environmental variables, using seasonal variability due to hydrological dynamics (i.e., the monsoon season). A field-based faunal survey was performed using standardized sampling techniques. Biodiversity was estimated using measures of species richness and measures of biodiversity based on the different diversity indices of Shannon-Wiener Index and Simpson's Index.